Penyebaran Penyakit Rabies pada Hewan Secara Spasial di Bali pada Tahun 2008-2011 (THE SPATIAL DISTRIBUTION OF RABID ANIMAL IN BALI DURING 2008-2011) - Batan, I Wayan; Lestyorini, Yunita; Milfa, Sri; Iffandi, Calvin; Nasution, Abdul Azis; Faiziah, Nurul; ., Rasdiyanah; Sobari, Imam; ., Herbert; Palgunadi, Ni Wayan Listyawati; Kardena, I Made; Widyastuti, Sri Kayati; et al. (Jurnal Veteriner; Vol 15 No 2 (2014), 2014)
Rabies is a new emerging disease in Bali. The first rabies case was reported in October 2008 atKedonganan and Jimbaran village, District of South Kuta, Badung regency. The rabies diseasehas now been distributed to all areas of Bali causing death of more than a hundred of human beingand thousands of dogs. The aim of the studies was to make a map of rabies distribution in Balibased on cases in animals (dog and Bali cattle) and human. The research was conducted bymaking a field surveys in nine regency of Bali. The surveys were focused on the occurrence ofhuman and animal rabies at the village level. The open ended questionaire was used in this surveyto collect data, and the secondary data also used in this study. Based on rabies disease mapping,it showed that the rabies have been distributed to eight regency and one city, covered 281 villagesout of 722 villages in Bali. In conclusion, the rabies had been distributed to all parts of Bali in threeyears periods.
Keywords: rabies in Bali, disease mapping